2019
DOI: 10.6026/97320630015090
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison on Some Interval Mapping Approaches for QTL Detection

Abstract: Quantitative trait locus (QTL) analysis is a statistical method that links two types of information such as phenotypic data (trait measurements) and genotypic data (usually molecular markers). There a number of QTL tools have been developed for gene linkage mapping. Standard Interval Mapping (SIM) or Simple Interval Mapping or Interval Mapping (IM), Haley Knott, Extended Haley Knott and Multiple Imputation (IMP) method when the single-QTL is unlinked and Composite Interval Mapping (CIM) is designed to map the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Several consistent minor-effect QTLs were also identified for amylose content, with the most significant QTL located on chromosome 8. QTLs are considered significant when above the threshold LOD score 3.0 [43]. Other research reported two QTLs on chromosomes 1 (markers RM8111-RM14323, LOD 2.03) and 9 (markers RM219-RM23914, LOD 2.88) for amylose content [44], as well three QTLs on chromosomes 8 (RM506-RM1235, LOD 2.57), 9 (RM219-RM23914, LOD 2.66) and 10 (RM24934-RM25128, LOD 6.13) for protein content in 120 doubled haploid (DH) rice population.…”
Section: Plos Onementioning
confidence: 99%
“…Several consistent minor-effect QTLs were also identified for amylose content, with the most significant QTL located on chromosome 8. QTLs are considered significant when above the threshold LOD score 3.0 [43]. Other research reported two QTLs on chromosomes 1 (markers RM8111-RM14323, LOD 2.03) and 9 (markers RM219-RM23914, LOD 2.88) for amylose content [44], as well three QTLs on chromosomes 8 (RM506-RM1235, LOD 2.57), 9 (RM219-RM23914, LOD 2.66) and 10 (RM24934-RM25128, LOD 6.13) for protein content in 120 doubled haploid (DH) rice population.…”
Section: Plos Onementioning
confidence: 99%
“…The next step is to perform a statistical analysis of the genotype-phenotype data to identify QTLs. The most commonly used method for QTL mapping is linkage analysis, which compares the phenotypic data with the molecular markers to identify regions of the genome that are associated with the phenotypic variation ( Akond et al, 2019 ). Once the QTLs are identified, further fine-mapping can be done to narrow down the chromosomal region relevant to the trait variation ( Raihan et al, 2016b ).…”
Section: Phase Ii: Molecular and Advanced Plant Breeding Technologymentioning
confidence: 99%
“…The remaining markers were binned according to their segregation patterns. After binning, we grouped the markers using a logarithm of odds (LOD) threshold of 3.0 [54]. Linkage groups were assigned according to the genomic position of the SNP markers determined during SNP calling.…”
Section: Maps Constructionmentioning
confidence: 99%